Design and evaluation of two proposed hybrid FCC-BCC lattice structures for enhanced mechanical performance - Shayan Rahimi; Mohsen Asghari (Heliyon)
Lattice structures are an innovative solution to increase the strength-to-weight ratio of a structure. In this study, two polymeric hybrid lattice structures—''FRB'' (a heterogenous structure which is indeed a BCC structure reinforced by FCC unit cells dispersed in a way to form a chessboard pattern in each layer) and the ''Multifunctional'' (a homogenous structure whose unit cells are a combination of FCC and BCC unit cells where their central nodes are connected)—are proposed, fabricated via liquid crystal display 3D printing technique, and their mechanical characteristics are evaluated under quasi-static loading, experimentally and numerically. The results indicate a 15.71 % increase in compressive strength and a 103.75 % improvement in volumetric energy absorption for the FRB structure compared to BCC. The Multifunctional structure revealed a 74.30 % increase in compressive strength along with a 111.30 % improvement in volumetric energy absorption compared to BCC, though it exhibited a 13.33 % decrease in specific energy absorption compared to the FCC structure. Both the proposed designs have merits; the FRB structure suitable for lightweight energy absorption and the Multifunctional structure appropriate for high load-bearing applications where the overall weight is not the primary concern.